Fluvial family health: work process of teams in riverside communities of the Brazilian Amazon - Maura Figueira; Dalvani Marques; Maria Vilela; Jessica Pereira; Jennifer Bazílio; Eliete Silva (Rural and Remote Health, 2020)
Introduction: This study aimed to understand and analyze the work process of fluvial family health teams in the context of riverside populations in the Brazilian Amazon. Methods: Action research was undertaken, conducting focus groups, individual interviews and participant observation with 27 workers of municipal teams of the state of Pará, in the Brazilian Amazon. The analysis was performed by the content, following the theoretical framework of the work process. Results: The following themes emerged: work object of the teams; work agents (who are the workers?); work technologies (the instruments of the process in fluvial health teams); and challenges for achieving the purpose of the work process. Conclusion: Recognition of the work object centered on the needs of the individual, family and community. The center for permanent education, supply of materials and inputs to the teams were implemented, and improved workflow for referring users was observed.